(untitled) (Revista Argentina de Cirugía, 2022)
Background: controversy exists regarding thyroidectomy as a definitive treatment for patients with hyperthyroidism. Objetive: to describe indications, pathologic findings and outcome of a series of consecutive patients who underwent total thyroidectomy due to hyperthyroidism. Methods: a retrospective observational study was done with 44 patients (34 female, 10 male) who un- derwent total thyroidectomy for different clinical manifestations of hyperthyoridism between January 2009 and October 2012 Results: most frequent surgical indications were multinodular goiter in 19 patients, hyperthyroid diffuse goiter in 11, oftalmopathy and diffuse goiter in 5 and suspected carcinoma in 4. Pathologic reports showed diffuse hyperplasia in 17 cases, multinodular goiter in 11, adenoma in 7, chronic lymphocitic thyroiditis in 4, papilar carcinoma in 3 and follicular carcinoma in 2. Postoperative complications were 3 symptomatic hypocalcemias and 2 transient dysphonias. Conclusions: total thyroidectomy as a treatment for hyperthyoridism in different clinical settings showed variable pathologic findings, including 11% of carcinoma, with a low transient complication rate.